Pengaruh Penggunaan Lapisan Aspal Karet Terhadap Kinerja Perkerasan Jalan Yang Berkelanjutan - Frendy Saputra; Rezi Munizar (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The escalating demands on road transport infrastructure require the development of resilient, sustainable pavement materials capable of withstanding heavy axle loads and climate extremes. This nonempirical research provides a comprehensive mechanistic synthesis demonstrating that elastomeric polymer integration significantly enhances binder viscosity, reduces penetration values, and elevates softening points. On a macrostructural level, these reological adjustments optimize volumetric parameters by systematically reducing air voids and reinforcing internal cohesion, which leads to a substantial increase in Marshall stability values. Mechanistic analysis indicates that rubber modified mixtures exhibit superior shear resistance and dynamic strain recovery, effectively minimizing rutting depth and extending the projected pavement service life from ten to fifteen years. This study successfully establishes a robust theoretical framework for the wider implementation of green infrastructure technologies within circular economy goals.